Navigating inclusivity and exclusivity in inter-religious relations - Hedges, Paul (2024)
By exploring the nuanced dynamics of inclusivity and exclusivity based on recent research, it is suggested that we need to delve into the interplay of these concepts within religious traditions in Singapore and reflect on the need for a balanced approach within diverse religious communities.